Perlindungan Hukum Pemegang Hak Cipta Terhadap Tindakan Penggandaan Atau Penggunaan Secara Komersial Ciptaan Berdasarkan Pasal 9 Undang-Undang No. 28 Tahun 2014 tentang Hak Cipta - Jeane Neltje; Diana Fitriana; Sarip (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Copying and commercial use of copyright (especially songs) is an act that is detrimental to copyright holders. Article 9 of the Copyright Law has emphasized this action and problems in the field of intellectual property protection become a fundamental problem when research shows that there are weaknesses in aspects of copyright protection. A copyrighted work will receive legal protection if it covers the fields of science, art and literature. Legal protection is obtained if a creation has been realized in a tangible form. The method used in this research is normative research. The author uses the library research method (library search) which is done by reading and studying written sources. According to Article 4 UUHC, the exclusive rights of protected music creators consist of moral rights and economic rights. Moral rights are inherent in the creator or actor that cannot be removed or deleted without any reason, even though the copyright or copyright has been transferred. However, not all countries provide the same legal protection for moral rights in copyright. Some countries may not have strong moral rights laws, or may provide less protection for those rights. Legal arrangements regarding the economic rights of creators or copyright holders show that economic rights are the exclusive rights of creators or copyright holders to obtain economic benefits from creations, so that everyone who exercises economic rights must obtain permission from the creator or copyright holder and is prohibited from duplicating and/or commercial use of works without the permission of the creator or copyright holder.